Body movement as an indicator of proceptive behavior in nurse sharks (Ginglymostoma cirratum) - Colbachini, Helen [UNESP]; Pizzutto, Cristiane Schilbach; Jorge-Neto, Pedro Nacib; Gutierrez, Rafael Caprioli; Gadig, Otto Bismarck Fazzano [UNESP] (Springer, 2020)
Nurse sharks are vulnerable of extinction in Brazil. Although its reproductive behavioral repertoire is already known, including indications that females are not passive to the attempts of males, no indication of proceptive behavior of females of this species is known. Considering that proceptive behavior is what initiates or increases the probability of a male exhibiting sexual behaviors directed at a female, the present study carried out behavioral observations in two groups of nurse sharks in reproductive period to identify possible proceptive behaviors. The present work identified a new behavior, here referred to as Body Movement (BM), as an indicator of proceptivity. This behavior corresponded on average to 47.68% of the reproductive behaviors performed by the females and its occurrence was positively correlated (r = 0.5143341 / p = 0.04152 - Spearman) with the occurrence of socio-reproductive behaviors of males. Being able to identify signs of proceptivity in animals is important to understand the reproductive context in which a group is found and to allow greater attention to animals that are able to reproduce, in order to create more efficient reproductive management programs to develop long-term sustainable population management.
Keywords: Copulatory behavior; Body movement; Courtship behavior; Reproductive behavior